2006
DOI: 10.1093/humrep/del058
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between first trimester fetal bone length and maternal serum pregnancy-associated plasma protein-A (PAPP-A)

Abstract: Maternal serum PAPP-A levels at 10-14 weeks of gestation are significantly associated with the length of fetal long bones such as humerus, femur and tibia. This provides further evidence that PAPP-A may be involved in the regulation of bone development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…PAPP‐A has now been correlated closely with fetal growth, especially growth of long bones, in laboratory and clinical studies24–29. This is consistent with studies which suggest that PAPP‐A represents a protein produced by human fibroblasts that helps activate an insulin‐like growth factor (IGF).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…PAPP‐A has now been correlated closely with fetal growth, especially growth of long bones, in laboratory and clinical studies24–29. This is consistent with studies which suggest that PAPP‐A represents a protein produced by human fibroblasts that helps activate an insulin‐like growth factor (IGF).…”
supporting
confidence: 68%
“…Other evidence from animal models suggests that PAPP‐A is involved in the regulation of bone development27. As supportive evidence, maternal serum PAPP‐A levels in the first trimester are associated with the length of fetal long bones22, 28, 29. Weisz et al 2 also found that isolated short femur length was highly associated with lower levels of PAPP‐A but not with levels of other analytes.…”
mentioning
confidence: 89%
“…In the present study, the performance of PAPP‐A levels for birth of a small fetus is better than that for PE, with higher ORs (Table ). It has been shown previously that maternal serum PAPP‐A levels are correlated with mid‐trimester long‐bone length . Previous publications have reported on the association of low PAPP‐A levels with birth of an SGA fetus (Table ).…”
Section: Discussionmentioning
confidence: 89%
“…PAPP‐A is a protease secreted by human fibroblasts which acts on insulin‐like growth factor‐binding protein‐4 and increases its bioactivity15. Recent studies have shown that PAPP‐A levels (at 11–14 weeks) are associated with femur length measured at the end of the first16 and second17 trimesters.…”
Section: Discussionmentioning
confidence: 99%